Low-gloss high-heat-resistance halogen-free flame-retardant PC / ABS alloy material and preparation method thereof

By optimizing the formulation and processing technology, a low-gloss, high-heat-resistant, halogen-free flame-retardant PC/ABS alloy material was prepared, solving the cost-effectiveness problem of balancing low gloss, heat resistance, and flame retardancy, and achieving excellent comprehensive performance.

CN119463447APending Publication Date: 2025-02-18中广核俊尔(浙江)新材料有限公司 +1

Patent Information

Application Number
CN202411743686.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing halogen-free flame-retardant PC/ABS materials, while maintaining low gloss and high heat resistance, struggle to simultaneously achieve excellent flame retardancy and a good cost-performance ratio.

Method used

By optimizing the formulation design, a compound of PC pure resin, ABS, talc, flame retardant, toughening agent, antioxidant, lubricant and anti-dripping agent is used, combined with talc and GMA grafted toughening agent from a specific manufacturer. The mixture is then mixed and processed using a twin-screw extruder to prepare a low-gloss, high-heat-resistant, halogen-free flame-retardant PC/ABS alloy material.

Benefits of technology

It achieves low gloss and high heat resistance while possessing excellent flame retardant and mechanical properties, offering excellent cost performance and making it suitable for electrical products and sports equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-gloss high-heat-resistance halogen-free flame-retardant PC / ABS alloy material and a preparation method thereof. The alloy material comprises the following raw materials in percentage by mass: 60%-90% of PC pure resin, 5%-10% of ABS pure resin, 1%-5% of talcum powder, 5%-10% of a flame retardant, 1%-5% of a flexibilizer, 0.2%-0.5% of an antioxidant, 0.2%-0.5% of a lubricant and 0.1%-0.5% of an anti-dripping agent. The invention also discloses a preparation method of the low-gloss high-heat-resistance halogen-free flame-retardant PC / ABS alloy material. The low-gloss high-heat-resistance halogen-free flame-retardant PC / ABS alloy material prepared by the invention has the advantages of low gloss, high heat resistance, favorable flame retardancy and favorable mechanical properties. The composite material can be widely applied to various fields such as automobile parts, electronic appliances, communication equipment, lighting equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS and a preparation method and application thereof. Background Art

[0002] PC / ABS alloy is an excellent engineering plastic made by melt blending PC and ABS. It has the advantages of both PC and ABS, making up for the defects of a single material, and greatly improving the comprehensive performance of the alloy material. Compared with ABS, it has improved mechanical properties such as high temperature resistance, impact strength and tensile strength; compared with PC, the melt viscosity, molding processability, paintability and melt fluidity of the blended alloy have been greatly improved. At the same time, because the addition of ABS has significantly reduced the cost of the product, it has developed rapidly in recent years and has been widely used in many fields such as automotive parts, electronic appliances, communication equipment, lighting equipment, office equipment, packaging materials, etc.

[0003] With the rapid development of the times, people's demand for the use of materials has gradually expanded, and the requirements have gradually become more stringent. In some fields, there are certain requirements for the glossiness of materials. In the field of electrical appliances, not only are materials required to have excellent flame retardant properties, but they are also required to have certain heat resistance. Among them, halogen-free flame retardant PC / ABS materials are selected due to their excellent mechanical properties and good injection molding fluidity.

[0004] The patent specification with publication number CN 106147190 A discloses a low-gloss, high-strength, halogen-free, flame-retardant PC / ASA blend material, characterized in that it includes the following raw materials by weight ratio: PC: 50-80 parts, ASA: 10-30 parts, halogen-free flame retardant: 10-20 parts, toughening agent: 1-10 parts, low-gloss agent: 1-10 parts, compatibilizer: 1-5 parts, anti-dripping agent: 0.1-1 parts, antioxidant: 0.2-2 parts, ultraviolet absorber: 0.2-2 parts, lubricant: 0.2-2 parts; the PC / ASA blend material described in the invention has low gloss performance and excellent mechanical properties and excellent flame retardant effect. The price of ASA in the invention is much higher than that of ABS, and the material lacks a certain cost-effectiveness. At the same time, CN 118374136 A involves a low-gloss PC / ABS composition and a preparation method thereof. The low-gloss PC / ABS composition is made of raw materials including the following components, measured in parts by weight: 32 to 75.6 parts of polycarbonate resin, 3 to 5 parts of compatibilizer, 20 to 50 parts of acrylonitrile-butadiene-styrene, 0.2 to 10 parts of matte masterbatch, 0.1 to 0.5 parts of antioxidant, 0.1 to 0.5 parts of lubricant, and 1 to 2 parts of black masterbatch; the low-gloss PC / ABS composition has a good matte effect while maintaining its excellent mechanical properties, and is particularly suitable for automotive interior decoration parts and home appliance exterior parts with high matte requirements, and can produce soft and uniform matte effects on both the glossy surface and the leather grain surface of the parts, but the material is not flame retardant, which limits its scope of use in some fields.

[0005] Based on the above characteristics, we have developed a low-gloss, high-heat-resistant, halogen-free and flame-retardant PC / ABS alloy material, which enables the material to have multiple functions while maintaining good mechanical properties and cost-effectiveness. Summary of the invention

[0006] In order to solve the problems existing in the above materials, the present invention provides a material having low gloss and high heat resistance as well as good flame retardant and mechanical properties through the design and optimization of the formula.

[0007] The technical solution adopted by the present invention is: A low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material and a preparation method thereof, comprising the following raw materials in percentage by mass: PC pure resin 60%-90% ABS 5%-10% Talc 1%-5% Flame retardant 5%-10% Toughener 1%-5% Antioxidant 0.2%%-0.5% Lubricant 0.2%-0.5% Anti-dripping agent 0.1%-0.5%.

[0008] In a low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, the melt index of the PC resin at 300°C and 1.2kg is 10g / 10min to 20g / 10min.

[0009] In a low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, the melt index of the ABS resin at 220° C. and 10 kg is 10 g / 10 min to 30 g / 10 min.

[0010] In a low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, the talc powder is one or more of 1250-10000 meshes; the preferred origin is Haicheng, Liaoning, the talc powder is provided by Xufeng Powder Company, and the talc powder addition amount is within 3%.

[0011] A low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, wherein the flame retardant is a sulfonate, silicon, phosphazene, phosphate ester flame retardant or a combination of several of them.

[0012] In a low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, the toughening agent is a compound of one or more of ABS high-rubber powder, MBS, ACR, EVA, and GMA grafted toughening agents; GMA grafted toughening agents are preferred, and the addition amount is within 6.5%.

[0013] In a low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, the antioxidant is compounded by a primary antioxidant and an auxiliary antioxidant in a mass ratio of 1: 1. The primary antioxidant is a hindered phenol antioxidant; the auxiliary antioxidant is at least one of a phosphite antioxidant and a thioester antioxidant.

[0014] In a low-gloss, high-heat-resistant, halogen-free and flame-retardant PC / ABS alloy material, the lubricant is a compound of one or more of fatty acid amide, fatty acid ester, fatty acid ester, paraffin and polyethylene wax.

[0015] In a low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material, the anti-dripping agent is an anti-dripping agent in which PTFE is coated with an SM / MMA composition, and is a highly fluid white particle with a particle size of 0.2 um and a PTFE content of 50 wt%.

[0016] A low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material and a preparation method thereof, comprising the following steps: 1. Fully dry the required raw materials; 2. Put PC and ABS raw materials, talcum powder, flame retardant and other additives into a stirring pot and stir for 5 minutes to mix them thoroughly; 3. Add the fully mixed mixture into a twin-screw extruder for extrusion at a speed of 350-450 r / min and a temperature of 220-250°C. After cooling in a water tank, pelletize and package to obtain the desired low-gloss, high-heat-resistant, halogen-free and flame-retardant PC / ABS alloy material.

[0017] The PC material prepared by the present invention can be used for electrical products, sports equipment, charging pile shells, etc.

[0018] Compared with the prior art, the low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material described in the present invention has the following advantages: The low-gloss, high-heat-resistant, halogen-free flame-retardant PC / ABS alloy material of the present invention has very low gloss. The use of a GMA grafted toughening agent and talcum powder produced in Haicheng, Liaoning Province can achieve the lowest gloss, higher heat deformation temperature and higher impact strength, and all aspects of performance are taken into consideration.

[0019] The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material of the present invention has excellent performance, and has high heat resistance and flame-retardant properties as well as excellent mechanical properties. DETAILED DESCRIPTION

[0020] The component grades used in Examples 1 to 8 and Comparative Examples 1 to 4 are as follows.

[0021] PC resin, the brand used is PC1609.

[0022] ABS resin, the brand used is ABS8391.

[0023] Talc powder 1 is 1250 mesh, produced in Haicheng, Liaoning, and provided by Xufeng Powder Company.

[0024] Talc 2 is 1250 mesh and is provided by Guangxi Longsheng Huamei Company.

[0025] The flame retardant is phosphazene flame retardant HPCTP.

[0026] Toughener 1 is a GMA grafted toughener Japanese BF-E.

[0027] Toughener 2 is an MBS toughener, specifically Romon & Haas EXL-2620.

[0028] The antioxidant is a compound of 1076 and 168 in a ratio of 1:1.

[0029] The lubricant is pentaerythritol ester (PETS).

[0030] The anti-dripping agent is an anti-dripping agent in which PTFE is coated with a SM / MMA composition. The anti-dripping agent is a highly fluid white particle with a particle size of 0.2 um and a PTFE content of 50 wt%.

[0031] Raw material / wt% Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 PC resin 79 79 79 79 79 79 76.5 74 84 81.8 69 82 ABS resin 10 10 10 10 10 10 10 10 10 10 10 10 Talc 1 5 2.5 2.5 5 5 5 5 2 Talc 2 2.5 2.5 Flame retardants 5 5 5 5 5 5 5 5 5 10 5 Toughener 1 5 2.5 2.5 2.5 5 2.5 5 Toughener 2 2.5 2.5 Antioxidants 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 Lubricants 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 Anti-drip agent 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 1. Dry the required raw materials thoroughly.

[0032] 2. Put the PC and ABS raw materials, the required talcum powder, flame retardant and other additives into a stirring pot and stir for 5 minutes to mix them thoroughly.

[0033] 3. Add the fully mixed mixture into a twin-screw extruder for extrusion at a speed of 350-450 r / min and a temperature of 220-250°C. After cooling in a water tank, pelletize and package to obtain the desired low-gloss, high-heat-resistant, halogen-free and flame-retardant PC / ABS alloy material.

[0034] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Izod notched impact strength KJ / m 2 > 15 61 57 60 49 52 46 52 55 54 52 43 UL-94(1.6mm) V0 V0 V0 V0 V0 V0 V0 V1 V0 HB V0 V0 Glossiness 35 42 13 31 21 29 9 7 89 10 9 51 Heat deformation temperature (1.8MPa) 112 110 111 109 111 109 110 108 113 115 106 113 The test method adopts GB / T test standard, such as gloss test adopts GB / T8807.

[0035] From Example 1 and Example 2 in the table and Comparative Example 1, we can see that adding talcum powder 1250 mesh alone and adding GMA grafted toughening agent BF-E alone can reduce the gloss of the material. From Example 1, it can be seen that the notch of the material is seriously reduced without the toughening agent BF-E, which shows that too much talcum powder will reduce the notch impact strength of the material.

[0036] From the comparison of Example 1, Example 2 and Example 3 in the table, it can be seen that when we use talcum powder 1250 mesh and toughening agent BF-E in combination, the glossiness of the material can be significantly reduced. It can be seen from Comparative Example 4 that by reducing the content of talcum powder, the notched impact strength of the material can also be significantly increased.

[0037] From the comparison of Example 1, Example 2 and Example 3 in the table, it can be seen that when we use talcum powder 1250 mesh and toughening agent BF-E in combination, the glossiness of the material can be significantly reduced. It can be seen from Comparative Example 4 that by reducing the content of talcum powder, the notched impact strength of the material can also be significantly increased.

[0038] From the examples 3 and 4 to 6 in the table, it can be seen that the flame retardancy and heat deformation temperature do not change or change too much when using talcum powder and different toughening agents from different manufacturers, but the glossiness and notched impact are different or obviously different. Haicheng talcum powder and GMA grafted toughening agent BF-E are preferred. The glossiness is below 20, the notched impact is above 50, the heat deformation temperature is above 110, and the flame retardancy is V0 level. The four properties are taken into account at the same time, which can fully meet the stringent requirements of some load-bearing structural parts that require a matte effect on the surface.

[0039] It can be seen from Comparative Example 2 in the table that when no flame retardant is added to the system, the heat deformation temperature of the material is 115°C. When the halogen-free flame retardant HPCTP is added, when V0 is reached in the embodiment, the heat deformation temperature of the material itself is less affected. It can be seen from Comparative Example 3, Embodiment 7 and Embodiment 8 that when the toughening agent content increases, the flame retardant performance of the material decreases. When we increase the content of the flame retardant to make the material reach V0, the heat deformation temperature does not show a significant decrease.

[0040] The low-gloss, high-heat-resistant, halogen-free and flame-retardant PC / ABS alloy material of the present invention has excellent comprehensive performance and has broad application prospects.

Claims

1. A low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material and a preparation method thereof, comprising the following raw materials in percentage by mass: PC pure resin 60%-90% ABS 5%-10% Talc 1%-5% Flame retardant 5%-10% Toughener 1%-5% Antioxidant 0.2%%-0.5% Lubricant 0.2%-0.5% Anti-dripping agent 0.1%-0.5%.

2. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The melt index of PC resin at 300°C and 1.2kg is 10g / 10min to 20g / 10min.

3. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The melt index of ABS resin at 220°C and 10kg is 10g / 10min to 30g / 10min.

4. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: Talc is one or a combination of several kinds of 1250-10000 mesh.

5. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The flame retardant is a combination of one or more of sulfonate, silicon, phosphazene and phosphate flame retardants.

6. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The toughening agent is a compound of one or more of ABS high rubber powder, MBS, ACR, EVA, and GMA grafted.

7. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The antioxidant is compounded by a primary antioxidant and an auxiliary antioxidant in a mass ratio of 1:

1. The primary antioxidant is a hindered phenol antioxidant; and the auxiliary antioxidant is at least one of a phosphite antioxidant and a thioester antioxidant.

8. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The lubricant is a compound of one or more of fatty acid amide, fatty acid ester, fatty acid ester, paraffin wax and polyethylene wax.

9. The low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material according to claim 1, characterized in that: The anti-dripping agent is an anti-dripping agent in which PTFE is coated with a SM / MMA composition. The anti-dripping agent is a highly fluid white particle with a particle size of 0.2 um and a PTFE content of 50 wt%.

10. A low-gloss, high-heat-resistant, halogen-free, flame-retardant PC / ABS alloy material and a preparation method thereof, characterized in that: The following steps are involved: (1) Fully dry the required raw materials; (2) Place PC and ABS raw materials, talcum powder, flame retardant and other additives in a stirring pot and stir for 5 minutes to allow them to be fully mixed; (3) Add the fully mixed mixture into a twin-screw extruder and extrude it at a speed of 350-450 r / min and a temperature of 220-250°C. After cooling in a water tank, pelletize and package to obtain the desired low-gloss, high-heat-resistant, halogen-free and flame-retardant PC / ABS alloy material.

Citation Information

Patent Citations

  • Low-gloss high-strength halogen-free flame retardant PC / ASA blending material and preparation method thereof

    CN106147190A

  • Low-gloss PC / ABS composition and preparation method thereof

    CN118374136A

  • High-heat-resistant high-rigidity halogen-free flame-retardant scratch-resistant PC-ABS (polycarbonate-acrylonitrile-butadiene-styrene) alloy material and preparation method thereof

    CN103724968A

  • High-impact heatproof halogen-free flame-retardant PC / ABS alloy material and preparation method thereof

    CN106905683A

  • Flame retardant PC / ABS alloy composition, preparation method therefor and application thereof

    WO2023061493A1

Cited By

  • Silica micropowder-talcum powder composite synergistic flame retardant as well as preparation method and application thereof

    CN122520980A